The changing village community - Halpern, Joel Martin (Modernization of traditional societies series, 1967)
It presents some general ideas about contemporary change in rural areas and offers concrete examples of changes in specific village communities throughout the world. No attempt is made to cover all geographic areas or all points of view. On the contrary, attention is focused on case studies and developments in a few countries, in order to raise certain questions about the nature and possible future significance of contemporary trends.